Characterizing Nuclear Fragmentation Reactions for Nuclear Physics Applications with the FOOT Experiment - Zarrella, Roberto (HNPS Advances in Nuclear Physics, 2025)
The cross-section measurement of nuclear fragmentation reactions of light nuclei (A < 20) is of great interest in current applied physics research. As a matter of fact, a complete understanding of such interactions would lead to an improvement in both Particle Therapy treatment planning systems and in risk-assessment for radiation exposure in long-term human Space missions. However, nuclear reaction databases lack the experimental measurements needed to accurately model nuclear fragmentation and, thus, calculations must rely on phenomenological models inherently subject to significant uncertainties. The FOOT (FragmentatiOn Of Target) experiment aims at a full characterization of the nuclear fragmentation reactions of interest for Particle Therapy and Radiation Protection in Space, i.e. in the energy range between 100 and 800 MeV/u. The experimental program comprehends an extensive set of measurements, in both direct and inverse kinematics, using ion beams and targets with composition similar to human tissues and spacecraft shielding materials. The final goal of FOOT is the measurement of double differential cross sections with respect to the emission angle and kinetic energy of the fragment with a precision better than 5%. The FOOT Collaboration has lately completed the development of the electronic apparatus, and several data acquisition campaigns have been already carried out with partial setups. This paper presents a brief overview of the current status of the experiment, together with a summary of the preliminary results obtained from the first measurements with 16O beams impinging on thin graphite targets.